Net locality : why location matters in a networked world - Gordon, Eric, 1973-; Silva, Adriana de Souza e. (Chichester, West Sussex : Wiley-Blackwell, 2011)
'The first book to provide an introduction to the new theory of Net Locality and the profound effect on individuals and societies when everything is located or locatable. Describes net locality as an emerging form of location awareness central to all aspects of digital media, from mobile phones to online maps to location-based social networks and games. Warns of the dangers that these technologies can present while also outlining the opportunities and the potential for pro-social developments. Provides a theory of the web, not just mobile devices.'--
'The web is all around us. The use of mobile phones and location-aware technologies and the ability for people to browse information from wherever they may be, means that physical location has become an important factor in how data is categorized and accessed. This book provides an introduction to the new theory of Net Locality, an emerging form of location awareness, a concept becoming central to cultural production and everyday life. Net locality is crucial to all aspects of digital media, from mobile phones to online maps to location-based social networks and games. This book describes what happens to individuals and societies when virtually everything is located or locatable and what they can do with this awareness, from organizing impromptu political protests to finding nearby friends and resources. It also covers the dangers these technologies and practices present, from challenging traditional notions of privacy to the reorganization of urban public space, whilst outlining the opportunities and the potential for pro-social developments'--
Includes bibliographical references and index.
Keywords: Digital communications; Integrated services digital networks; Wireless communication systems; World Wide Web; Internet -- Technological innovations; Digital communications -- Social aspects